2014
DOI: 10.1093/scan/nsu041
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure links trait creativity to openness to experience

Abstract: Creativity is crucial to the progression of human civilization and has led to important scientific discoveries. Especially, individuals are more likely to have scientific discoveries if they possess certain personality traits of creativity (trait creativity), including imagination, curiosity, challenge and risk-taking. This study used voxel-based morphometry to identify the brain regions underlying individual differences in trait creativity, as measured by the Williams creativity aptitude test, in a large samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 115 publications
5
84
0
1
Order By: Relevance
“…Neuroimaging research has shown that Openness is associated with individual variation in the structure and function of specific DN regions (Adelstein et al, ; Beaty et al, ; Li et al, ; Passamonti et al, ). Recently, Beaty et al () assessed the contribution of Openness to DN functional connectivity using graph theoretical analysis of resting‐state fMRI data.…”
Section: Imagination and Brain Dynamicsmentioning
confidence: 99%
“…Neuroimaging research has shown that Openness is associated with individual variation in the structure and function of specific DN regions (Adelstein et al, ; Beaty et al, ; Li et al, ; Passamonti et al, ). Recently, Beaty et al () assessed the contribution of Openness to DN functional connectivity using graph theoretical analysis of resting‐state fMRI data.…”
Section: Imagination and Brain Dynamicsmentioning
confidence: 99%
“…Among the commonly used creativity tests, the most famous ones are Torrance Tests of Creative Thinking (TTCT) and The Williams Creativity Assessment Packet revised by Lin & Wang (1994), which can be used to evaluate creative thinking. The Williams Creativity Assessment Packet has been extensively applied in the teaching activities of various domains, such as performing arts courses, music courses and science teaching, and most creativity-related studies have demonstrated positive results (Jin, Wang, & Dong, 2016;Li et al, 2014;Wang & Cheng, 2016).…”
Section: Press/placementioning
confidence: 99%
“…Li et al, 2014;Song et al, 2014;Wang et al, 2014). Participants were instructed to undertake a series of computer-based cognitive ability tests, paper-pencil questionnaires, and MRI scans.…”
Section: Participantsmentioning
confidence: 99%
“…Studies have shown that the VBM methodology can be used to investigate the neural basis of individual differences in behavioral performance (e.g., personality characteristics) (DeYoung et al, 2010;Kanai and Rees, 2011;Kong et al, 2014;Song et al, 2014;Takeuchi et al, 2014). Based on the previous neuroscience findings on individual well-being (Heller et al, 2013;Takeuchi et al, 2014;Urry et al, 2004;van Reekum et al, 2007), we hypothesized that individual differences in social well-being would be associated with rGMV in the PFC regions (e.g., DLPFC, DMPFC) that has been linked to cognitive-emotional functions (Alvarez and Emory, 2006;Curtis and D'Esposito, 2003;Ochsner and Gross, 2005).…”
Section: Introductionmentioning
confidence: 99%